Comprehensive study of Tilapia skin collagen peptide on ileal injury and intestinal flora in rats induced by high altitude hypoxia - Jingyi Wang; Hao Wang; Chunxia Li; Xiaojuan Zhang; Jin Liu; Yanzhou Hu; Ping Qian (Journal of Functional Foods)
Acute high-altitude hypoxia is typically linked to intestinal injury and dysbiosis of the gut microbiota. Thus, the aims of this study were to investigate the effects of Tilapia skin collagen peptide (CP) on inflammatory response, antioxidant systems, intestinal barrier function, and intestinal flora in rats exposed to high altitude hypoxia condition. Additionally, a Nano liquid chromatography-tandem mass spectrometry (nano LC-MS/MS) and virtual screening were employed to identify specific peptides that could be functionally significant. The results showed that CP could reduce the Disease active index (DAI), increase the mRNA expression level of tight junction protein, and reduce the content of D-lactic acid (D-LA) and Diamine oxidase (DAO) in the serum of rats, and thus alleviate the mechanical injury of intestinal mucosa induced by hypoxia. In addition, CP improved hypoxia-induced intestinal inflammation by significantly down-regulating pro-inflammatory cytokines (IL-6, IL-12, TNF-α and CRP). Furthermore, CP significantly up-regulated the an tioxidant enzymes SOD and GSH-Px and down-regulated MDA in the serum of rats, and improved hypoxia-induced oxidative stress. 16S rDNA sequencing of the intestinal flora revealed that CP significantly reduced the abundance of the pathogenic bacterium Escherichia, increased the abundance of the beneficial bacterium Limosilactobacillu, and significantly increased the levels of acetic acid, isobutyric acid, and isovaleric acid in feces. Five potential anti-inflammatory peptides were identified including AGFF, FGLGFF, LGLF, LGFL and LFGF by nano LC-MS/MS technology and virtual screening. Molecular docking analysis revealed that these screened peptides can competitively interrupt the formation of TNF-α. Consequently, CP effectively alleviates hypoxia-induced intestinal barrier injury in rats by reducing inflammation, oxidative stress, and modifying intestinal flora and its metabolites.